Development of a scoring tool (BLARt score) to predict functional outcome in lower limb amputees. Issue 19 (11th September 2019) - Bowrey, Sarah; Naylor, Helen; Russell, Pip; Thompson, Jonathan
Abstract: Purpose: To develop a valid preoperative scoring tool that predicts the probability of walking with a prosthetic limb after major lower limb amputation. Methods: A retrospective review of 338 patients who had undergone lower limb amputation was conducted to identify characteristics that affected the success of rehabilitation with a prosthetic limb. These data were used to devise an assessment tool (the BLARt score), which was then tested and validated in 199 patients planned to undergo lower limb amputation in two UK regional centers. Functional rehabilitation outcomes were recorded at 12 months after surgery using the SIGAM mobility grading. Results: No patient with a BLARt score ≥13 achieved good functional outcome (defined as independent mobility, SIGAM grade E or F) and only 6 patients with a BLARt score ≥17 achieved any functional outcome (defined as any ability to walk unaided, SIGAM grade C or greater). Conclusions: In the patient cohorts studied, the BLARt assessment tool was a strong predictor of whether or not patients would be able to walk with a prosthetic limb after surgery. It is simple to administer and could be useful in clinical practice to inform expectations for patients and clinicians. Implications for rehabilitation: Patients undergoing lower limb amputation face major physical and psychological challenges after surgery that have a considerable impact on rehabilitation and their ability to walk independently. Many amputees are unable to walk with a prosthetic limb, but there are no validated tools to predict this before surgery. The BLARt is a potentially valuable measure that can predict the likelihood of being unable to walk after amputation. It is simple to use and could be useful to inform patients' and clinicians' expectations before surgery.